Ruzigrass affecting soil‑phosphorus availability - Merlin, Alexandre; He, Zhenli Li; Rosolem, Ciro Antonio (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effectiveness of ruzigrass (Urochloa ruziziensis) in enhancing soil‑P availability in areas fertilized with soluble or reactive rock phosphates. The area had been cropped for five years under no‑till, in a system involving soybean, triticale/black‑oat, and pearl millet. Previously to the five‑year cultivation period, corrective phosphorus fertilization was applied once on soil surface, at 0.0 and 80 kg ha-1 P2O5, as triple superphosphate or Arad rock phosphate. After this five‑year period, plots received the same corrective P fertilization as before and ruzigrass was introduced to the cropping system in the stead of the other cover crops. Soil samples were taken (0–10 cm) after ruzigrass cultivation and subjected to soil‑P fractionation. Soybean was grown thereafter without P application to seed furrow. Phosphorus availability in plots with ruzigrass was compared to the ones with spontaneous vegetation for two years. Ruzigrass cultivation increased inorganic (resin‑extracted) and organic (NaHCO3) soil P, as well as P concentration in soybean leaves, regardless of the P source. However, soybean yield did not increase significantly due to ruzigrass introduction to the cropping system. Soil‑P availability did not differ between soluble and reactive P sources. Ruzigrass increases soil‑P availability, especially where corrective P fertilization is performed.
Keywords: Brachiaria ruziziensis; Urochloa ruziziensis; cover crops; crop rotation; P cycling; phosphorus fractionation